2014
DOI: 10.1542/peds.2013-2207
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Head Growth in Preterm Infants: A Randomized Controlled Parenteral Nutrition Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Preterm infants dependent on parenteral nutrition are vulnerable to deficits in early postnatal nutritional intake. This coincides with a period of suboptimal head growth. Observational studies indicate that poor nutritional intake is associated with suboptimal head growth and neurodevelopmental outcome. WHAT THIS STUDY ADDS:This study provides randomized controlled trial evidence that head growth failure in the first 4 weeks of life can be ameliorated with early nutritional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 45 publications
6
149
1
2
Order By: Relevance
“…The observation is at odds with the Standardised, Concentrated Additional Macronutrients, Parenteral nutrition in very preterm infants (SCAMP) study, in which very preterm neonates randomised to receive higher PN from birth had a larger head circumference at 28 days. 68 Of note is that, although the SCAMP study aimed to deliver large amounts of PN, randomisation occurred up to 120 hours of age (compared with 24 hours in the NEON trial) and hence infants received a lower average energy and amino acid intake over the first 3 postnatal days than the NEON trial infants. The NEON trial was not powered to detect a difference in head circumference, but our observation is a concern as the possibility of adverse effects from higher PN has been raised previously.…”
Section: Resultsmentioning
confidence: 99%
“…The observation is at odds with the Standardised, Concentrated Additional Macronutrients, Parenteral nutrition in very preterm infants (SCAMP) study, in which very preterm neonates randomised to receive higher PN from birth had a larger head circumference at 28 days. 68 Of note is that, although the SCAMP study aimed to deliver large amounts of PN, randomisation occurred up to 120 hours of age (compared with 24 hours in the NEON trial) and hence infants received a lower average energy and amino acid intake over the first 3 postnatal days than the NEON trial infants. The NEON trial was not powered to detect a difference in head circumference, but our observation is a concern as the possibility of adverse effects from higher PN has been raised previously.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown the advantages of early nutrition and avoidance of protein deficits (10,(13)(14)(15). However, provision of adequate nutrition in the early postnatal period remains a challenge, and current clinical practices for the delivery of adequate nutrition may be insufficient (8,9,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of very-low-birth-weight infants, an optimized parenteral nutrition regimen with increased protein improved early postnatal head growth compared to a standard parenteral nutrition regimen (10), suggesting that improvement of clinical nutrition practices may be crucial in improving outcomes for premature infants. Failure to "catch up" in the first 8 mo of life is associated with lower head circumference and higher rates of poor neurologic development in very-lowbirth-weight infants (11).…”
mentioning
confidence: 99%
“…During hospitalization increased protein intake improves head growth in preterm infants (66,67). Even so total energy and lipid intake also have been positively correlated with head growth (67,68).…”
Section: The Role Of Dietary Proteins In Neurodevelopmentmentioning
confidence: 99%
“…Even so total energy and lipid intake also have been positively correlated with head growth (67,68). Nonetheless, Hansen-Pupp et al could not associate protein and caloric intake with brain volumes (39) and in several studies protein-enriched nutrition failed to improve neurodevelopmental outcome up to 18 mo corrected age (53,66,69,70).…”
Section: The Role Of Dietary Proteins In Neurodevelopmentmentioning
confidence: 99%